Recent Results on Time-Delay Systems Analysis and Control - Witrant, Emmanuel; Fridman, Emilia; Sename, Olivier; Dugard, Luc.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book mostly results from a selection of papers presented during the 11th IFAC (International Federation of Automatic Control) Workshop on Time-Delay Systems, which took place in Grenoble, France, February 4 - 6, 2013. During this event, 37 papers were presented. Taking into account the reviewers' evaluation and the papers' presentation the best papers have been selected and collected into the present volume. The authors of 13 selected papers were invited to participate to this book and provided a more detailed and improved version of the conference paper. To enrich the book, three more chapters have been included from specialists on time-delay systems who presented their work during the 52nd IEEE Conference on Decision and Control, which held in December 10 - 13, 2013, at Florence, Italy. The content of the book is divided into four main parts as follows: Modeling, Stability analysis, Stabilization and control, and Input-delay systems. Focusing on various topics of time-delay systems, this book will be interesting for researchers and graduate students working on control and system theory. .
Part I Modelling -- Part II Stability Analysis -- Part III Stabilization and Control -- Part IV Input-delay Systems.
Keywords: Control engineering; System theory; Control theory; Differential equations; Control and Systems Theory; Systems Theory, Control; Differential Equations